2016
DOI: 10.1016/j.ijgo.2015.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal practices among HIV‐negative female sex workers along the US–Mexico border and their implications for emerging HIV prevention interventions

Abstract: Objective To describe intravaginal practices (IVPs) among female sex workers (FSWs) who inject drugs in two cities—Tijuana and Ciudad Juarez—on the border between the USA and Mexico. Methods Data for a secondary analysis were obtained from interviews conducted as part of a randomized controlled trial in FSWs who injected drugs between October 28, 2008, and May 31, 2010. Eligible individuals were aged at least 18 years and reported sharing injection equipment and having unprotected sex with clients in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
6
3
Order By: Relevance
“…It is important to note that our results differ in several ways from those reported by a previous study that examined intravaginal practices among FSWs in Tijuana and Ciudad Juarez [ 28 ]. In contrast to FSWs included in our study, in the previous study, a greater proportion of FSWs in Ciudad Juarez (53%) than in Tijuana (33%) reported performing intravaginal practices in the past 6 months [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…It is important to note that our results differ in several ways from those reported by a previous study that examined intravaginal practices among FSWs in Tijuana and Ciudad Juarez [ 28 ]. In contrast to FSWs included in our study, in the previous study, a greater proportion of FSWs in Ciudad Juarez (53%) than in Tijuana (33%) reported performing intravaginal practices in the past 6 months [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It is important to note that our results differ in several ways from those reported by a previous study that examined intravaginal practices among FSWs in Tijuana and Ciudad Juarez [ 28 ]. In contrast to FSWs included in our study, in the previous study, a greater proportion of FSWs in Ciudad Juarez (53%) than in Tijuana (33%) reported performing intravaginal practices in the past 6 months [ 28 ]. Furthermore, while data on the use of commercial solutions were not reported by the previous study, unlike our findings with respect to the use of non-commercial solutions for vaginal washing, the previous study found that use of homemade solutions for intravaginal practices was higher in Ciudad Juarez (79%) than in Tijuana (30%) [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations